Variation of the SOFA score and mortality in patients with severe burns: A cohort study. Issue 1 (February 2023) - Calles, Julien; Cohen, Benjamin; Forme, Nathalie; Guendil, Zahida; Fermier, Brice; Chassier, Claire; Elkrief, Laure; Roquilly, Antoine; Remerand, Francis; Miguel Montanes, Romain
Abstract: Multiple organ failure (MOF) is the leading cause of death in patients with burns requiring ICU admission. Quantifying the evolution of MOF, with the SOFA score, over the first few days after a severe burn may provide useful prognostic information. This retrospective cohort study aimed at evaluating the association between the evolution of the SOFA score between day 0 and day 3 and in-hospital mortality. All patients admitted for severe burns at the burn ICU of the Tours University Hospital between 2017 and 2020 and who stayed 3 days or more were included. Severe burns included: total body surface area burned (TBSA) ≥ 20 % or burns of any surface associated with one or more of the following items: (1) organ failure, (2) clinically significant smoke inhalation and/or cyanide poisoning, (3) severe preexisting comorbidities, (4) complex and specialized burn wound care. DeltaSOFA was defined as day 3 minus day 0 SOFA. One hundred and thirty-six patients were included. Median age was 52 years (38−70), median TBSA burned was 24 % (20−38), median day 0 SOFA was 2 (0−4) and median day 3 SOFA was 1 (0−5). In-hospital mortality was 10 %. There was a significant association between deltaSOFA and mortality that persisted after adjustment for age and TBSA (HR 1.37, 95 %CI 1.09–1.72, p  < 0.01). Area under the receiver operating characteristics curve for the prediction of mortality by day 0 SOFA and deltaSOFA were 0.79 (95 %CI 0.69–0.89) and 0.83 (95 %CI 0.70–0.95) respectively. After exclusion of patients with TBSA burned< 15 %, deltaSOFA remained independently associated with mortality (HR 1.42 95 %CI 1.09–1.85, p  < 0.01). In addition, SOFA variations allowed the identification of subgroups of patients with either very low or very high mortality. In patients with severe burns, SOFA score evolution between day 0 and day 3 may be useful for individualized medical and ethical decisions. Further multicenter studies are required to corroborate the present results. Highlights: SOFA score variation is associated with in-hospital mortality in patients with severe burns. SOFA score variation identifies subgroups with low mortality in patients with severe burns. SOFA score variation may help for ethical decisions in patients with severe burns.